A-28 Updated Baselines Show Improvement, Even When Athletes Sustain A Concussion Between Assessments. (18th June 2020) - O'Connor, S; Dean, T; Schatz, P
Abstract: Objective: To explore change across repeated baseline assessments using raw scores and percentile scores, for athletes sustaining and not sustaining a concussion between baselines. Method: Athletes (12–23 years) completed two valid, baseline neurocognitive test sessions using ImPACT. Participants were divided into independent groups based on having sustained a concussion between annual baselines (CONCUSSION; N = 269) or no concussion (NO CONCUSSION; N = 270) between baselines. Raw change scores were calculated between the first and follow-up baseline for both groups by subtracting the first baseline score from the updated baseline score on the four ImPACT composite scores. Age- and gender-based percentile scores were then applied for all participants, and percentile change scores were calculated in the same manner. Raw change scores and percentile change scores between groups were compared using 4 ANOVAs with a Bonferroni-corrected p-value of (p < .0125). Results: Using raw scores ANOVAs revealed that athletes in the CONCUSSION group showed significantly greater improvement on follow-up testing than athletes in the NO CONCUSSION group on Verbal Memory (p < .001) and Visual Motor Speed (p = .001), but not on Visual Memory (p = .41) and Reaction Time (p = .04). Using percentile ranks, ANOVAs revealed significantly greater improvement in CONCUSSION group on Verbal Memory (p < .001), but not on Visual Memory (p = .34), Visual Motor Speed (p = .03), or Reaction Time (p = .014). Conclusions: Athletes sustaining a concussion between annual baseline assessments show increases on Verbal Memory and Visual Motor Speed follow-up testing when using raw composite scores, but only on Verbal Memory when using age- and gender-based percentile ranks.